EFFECTIVE COMMUNICATION: THE IMPORTANCE OF COMMUNICATION BETWEEN COACHES AND PLAYERS FOR ENHANCING UNDERSTANDING AND PERFORMANCE ON THE FIELD - Benevides, Alex Tadeu (Revista Sistemática, 2021)
Effective communication between coaches and athletes plays a crucial role in enhancing individual performance and fostering collective success in sports. This article explores how verbal and non-verbal communication strategies impact athletes’ understanding, motivation, and on-field behavior. Drawing on empirical research, it highlights the importance of personalized communication, emotionally intelligent coaching, and cultural sensitivity in building trust and improving athletic outcomes. Furthermore, the use of feedback and modern technologies, such as video analysis, is discussed as a means of refining communication and accelerating learning. The findings suggest that coaches who prioritize clear, adaptive, and supportive communication are better positioned to develop athletes’ potential and achieve consistent performance improvements.